(untitled) (Eurasian Journal of Learning and Academic Teaching, 2021)
The article briefly describes the theoretical issues of semantics and scientific observations of its development. The science of semiotics, which originated in French linguistics and developed in world linguistics, is becoming the most comprehensive and important object of modern comparative linguistics.